Christ and Creation in the Synoptic Gospels - Barton, Stephen C. (Journal for the study of the New Testament, 2025)
Observing that most scholarly attention to the theme of Christ and creation has taken place in Pauline and Johannine studies, this essay addresses a relatively neglected factor in Synoptic studies. On the assumption that, scripturally speaking, ‘creation’ is a relational category in terms of which time, space, persons, and values are interpreted in relation to God in God’s sovereignty, the essay draws attention to the multiple ways creation, interpreted christologically and eschatologically, shapes the Evangelists’ portraits of Jesus both literarily and theologically. The main conclusion is that creation, including stories of the beginnings of the world and of the people of Israel, offers the Evangelists significant ways to speak about the meaning of history and human existence as given by God in the life, death, resurrection, and ascension of God’s Son. This revelation is understood as ultimate victory in the battle against the forces of chaos and death and as the inauguration of a redeemed sociality.